Associations of procrastination with loneliness, social isolation, and social withdrawal - Hajek A.; Gyasi R. M.; Pengpid S.; Kostev K.; SOYSAL P.; Veronese N.; Smith L.; Jacob L.; König H.; Peltzer K. (My University, 2025)
Aim: The aim was to investigate the association of procrastination with loneliness, social isolation, and social withdrawal (also stratified by sex). Subjects and methods: Data were used from a large sample of the general adult population in Germany, consisting of individuals aged 18 to 74 years (analytic sample, n = 5000 individuals, mean age: 46.9 years, SD: 15.2; 50.7% female). Standardized instruments were employed to measure the key variables. Multiple linear regressions were employed. Results: After the adjustment for various sociodemographic factors, lifestyle habits, and health-related variables, the regression analyses showed that greater procrastination was significantly associated with higher levels of loneliness (β =.11, p <.001), higher perceived social isolation (β =.05, p <.001), higher objective social isolation (β =.14, p <.001), and greater social withdrawal (β = 1.00, p <.001). Additional regressions showed that such associations were mainly significantly more pronounced among men. Conclusion: Our study showed that procrastination is associated with several unfavorable social outcomes, particularly among men. Efforts to address procrastination may also help such unfavorable social outcomes, pending future longitudinal studies.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; Sosyal Bilimler (Soc); Sosyal Bilimler Genel; Kamu Çevre Ve İş Sağlığı; Social Sciences (Soc); Social Sciences General; Public Environmental & Occupational Health; Halk, Çevre ve İş Sağlığı; Sağlık Bilimleri; Public Health, Environmental and Occupational Health; Health Sciences; Delaying; Hikikomori; Loneliness; Postponement; Procrastination; Social exclusion; Social isolation